Perspektif Perempuan Terhadap Prostitusi - Nadia Putri Pascawati (Darma Cendika Catholic University, 2019)
Women in the world of prostitution are unwittingly becoming things that are rife. The world of prostitution is divided into several social classes. Talking about prostitution must also talk about social class. The law guarantees a decent livelihood, and is equally in the eyes of the law for each of its citizens. As mandated by Article 27 of the 1945 Constitution of the Republic of Indonesia concerning Human Rights. Besides that women are considered as weak creatures that can be traded is a perspective that we must all fight. Many history books say that being a woman means being a jewelry for men. Such thoughts weaken women's mentality. Though many laws in Indonesia protect women's rights. As a result, many women are desperate and choose a shortcut to survive by entering the world of prostitution. Positive law in Indonesia only regulates people who trade other people. While trafficked persons are not subject to any punishment. In fact, many people in the community that occur are trafficked people actively ask pimps to trade. The change in Law Number 21 of 2007 to impose sanctions on prostitutes is expected to be a form of strong warning to eradicate prostitution itself. It should be realized that in prostitution women not only act as victims but also as perpetrators. If there are no perpetrators, the act of prostitution will also not exist. So that not only pimps and service users are the legal targets while women who offer themselves are protected by law and are considered victims, while the fact is that these women do not qualify as victims who are under duress or threats of violence. In reality, prostitution exists and will continue to exist even though we make regulations to prohibit its existence, even prostitution has involved underage children whose rights should be protected by the surrounding adults. In such conditions, it is best for us to make regulations to regulate it. So, prostitution can still be done but the conditions of its implementation must be clearly defined in the law. In this scientific work using the method of library data collection techniques from primary and secondary data with descriptive data analysis.